The Effect of Carbon Performance on Firm Value and Moderating Role of Ownership Concentration and Public Visibility - Hanifah, Siti Nurul; Ratna Wardhani (Riset Akuntansi dan Keuangan Indonesia, 2025)
With the increasing awareness of stakeholders and climate change issues, companies increasingly tries to manage their emissions. This study aims to examine how carbon emissions performance effects firm value and to examine the moderating role of ownership concentration and public visibility. This study uses a data set of 52 companies with 206 observations in non-financial companies listed on the Indonesia Stock Exchange during 2016-2023. The results show that carbon emission performance has a positive effect on firm value and ownership concentration cannot moderate the relationship, but public visibility can weaken the relationship between carbon emission performance and firm value. This research implies the importance of companies managing carbon emissions as a business sustainability strategy that can attract investors and maintain public visibility to avoid environmental controversy.